UPAYA PELESTARIAN KEBUDAYAAN JAWA MELALUI PROGRAM NGURI-NGURI BUDAYA JAWA PADA ANAK USIA DINI - Rosyida, Hamda Anzila; Afrih Lia, Naila Fikrina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to describe efforts to preserve local culture among early childhood students through the Nguri-Nguri Budaya Jawa Program. This study employed a qualitative method with a descriptive-analytical approach and was conducted at RA IT Nurul Islam, as the institution had already implemented this program during the even semester. The research subjects included the school principal and two teachers who served as program implementers. Data collection techniques were conducted through observation, interviews, and documentation over a two-month period, with data analysis using the Miles and Huberman model. The results of the study indicate that the preservation of local culture is systematically integrated into learning through various Javanese culture-based strategies, such as daily activities involving the use of the Javanese language in interactions, traditional songs and games, and specific activities, such as cultural literacy, traditional games, as well as arts and creativity activities. The implementation of this program not only introduces culture symbolically but also internalizes cultural values within children’s learning. The program’s success is supported by the consistent integration of culture into learning activities, teacher creativity, and institutional support from the school. The Nguri-Nguri Budaya Jawa program makes a significant contribution as an effective and sustainable strategy for preserving Javanese culture, thereby strengthening the formation of children’s cultural identity from an early age.